Analisis Logam Fe dengan Teknik Voltammetri Pelucutan Anodik Pulsa Diferensial dalam Tanaman Pakcoy dari Perkebunan Sayur Bedugul Bali - Irdhawati Irdhawati; Rosanti Suryani Tince Mbatu; Emmy Sahara (Jurnal Kimia Valensi, 2018)
Pakcoy is one of the most popular vegetable. The use of synthetic fertilizers and pesticides contain heavy metals can contaminate pakcoy vegetable. This research aims to determine the validity of measurements and concentration of Fe in pakcoy using differential pulse anodic stripping voltammetry technique.The working, reference, and counter electrodes were platinum disk, Ag/AgCl, and Pt wire, respectively. The optimum measurement results of the standard solutions of Fe(III) obtained the optimum deposition time was 70 seconds, the optimum scan rate was 10 mV/s, and the optimum deposition potential at -0.47 V. A linear concentration of standard solution of Fe(III) observed at the range of 50 ppb~500 ppb, with correlation coefficient 0.9954. Limit of detection was 50.18 ppb. The repetition of 10 times measurements had a Horwitz ratio of less than 2. Percent recovery was 100.26% ± 0.27%. The average of Fe(III) concentration in the samples from 5 (five) locations of the pakcoy sampling contains 3.82±0.29 ppm, less than SNI treshold line of 5.0 ppm.